El control interno contable al grupo de efectivo y equivalente de efectivo y su aporte a la razonabilidad de los estados financieros - Jimenez Guerrero, Andrea Karina (2015)
Over time organizations have grown to significant steps, and control of their operations became vulnerable, so they were in the need to create internal control system to prevent risks affecting the financial stability of the organization; allowing the achievement of objectives, without any fraud. This research project was aimed to use the tool of internal control in the group cash and cash equivalents, to diagnose the needs that the company needs to improve its record in this area, getting reasonableness of the financial statements. This research was supported a thorough study of the documentation that the company owns, sustaining the operations for the period 2014. The main contribution of the research is to propose a series of strategic guidelines based on the needs found; preventing future risks, to disqualify the company. Developing a proposal to improve the internal control of Go Cash and cash equivalents, in compliance with current regulations. Beside the contribution that research makes to the different areas as Technical and Economic Social will reveal methods and procedures to improve the economic status of organizations in general and their and social environment.